The media's agenda setting in manipulating audience's psychology through Ferdy Sambo's case - Ira Lusiawati (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The media not only presents the text written in the script that is distributed throughout its network, but also highlights dramatic elements that serve as "spices" to manipulate the audience's psychology. In reporting the Ferdy Sambo case, one of the strategies used is the agenda setting technique. Through this method, news is structured to provide a specific mental reaction to the audience's interaction with the media. In the initial news of the uproar over an incident, the important points that need to be highlighted for the audience's consumption are emphasized. This is followed by related news that is considered to be very important in filling the audience's agenda. Based on the media's techniques used, this study aims to determine how the media manipulates the audience's psychology. To obtain appropriate results, this research uses a descriptive qualitative method that is directed to obtain clear information based on high credibility online media platforms. The results of the study show that three online media, namely kompas.com, detik.com, and tribunnews.com, apply the agenda setting technique to shape the public agenda by emphasizing the distributed script.